1978
DOI: 10.1159/000155829
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Morphology of Lemur variegatus

Abstract: The middle ear morphology of Lemur variegatus, a strepsirhine primate, is described. Although no promontory branch of the internal carotid artery appears, there is a well-developed ‘promontory canal’ containing a nerve trunk. This structure, which is previously undescribed in strepsirhines, is made up of the tympanic nerve and the internal carotid nerve. The implications of this discovery for paleontology, systematics, and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The ventral surface of the petrosal is scoured by a slight transpromontorial sulcus. This sulcus corresponds to direct contact by the ICA of non-artiodactylan mammals [52][53][54][55][56][57]; however, in the adult alpaca, the ICA does not make direct contact with the petrosal. The presence of a transpromontorial sulcus in adult alpacas may be an effect of arterial reduction during ontogeny (see below).…”
Section: Methodsmentioning
confidence: 99%
“…The ventral surface of the petrosal is scoured by a slight transpromontorial sulcus. This sulcus corresponds to direct contact by the ICA of non-artiodactylan mammals [52][53][54][55][56][57]; however, in the adult alpaca, the ICA does not make direct contact with the petrosal. The presence of a transpromontorial sulcus in adult alpacas may be an effect of arterial reduction during ontogeny (see below).…”
Section: Methodsmentioning
confidence: 99%
“…The significance of this variation for primate systematics will not be clear until we have a better understanding of variation in the carotid canals of modern lemuroids. Conroy and Wible (1978) have shown that the promontory canal does not always carry a promontory branch of the internal carotid artery in extant lemuroids, and Hill (1953) found that the stapedial canal in Tarsius does not always house a stapedial branch of the internal carotid artery. These discoveries do not bear directly on the systematic interpretation of fossils, which are based on the canals in any case, but they do affect our interpretation of possible functional differences between the carotid circulatory patterns of various living and fossil prosimians.…”
Section: Auditory Regionmentioning
confidence: 99%
“…In modern lemurs that possess intact internal carotid systems, such as Eulemur and Lepilemur, ossification of the canal tends to be less complete, and the artery's track across the promontorium is mostly unenclosed by bone. Some notion of the variation found in extant lemurs can be gained by examining the schematic drawings of Szalay and Katz (1973) (see also Conroy and Wible, 1978). There are few known cranial specimens of adapids (e.g., Leptadapis) with well-preserved basicrania, and the range of variation in this group remains unclear.…”
Section: Discussion With These Features and Identifications In Mindmentioning
confidence: 99%